The Asia Pacific cohort studies collaboration: A decade of achievements - Woodward, M.; Huxley, Rachel; Ueshima, H.; Fang, X.; Kim, H.; Lam, T. (2012)
The Asia Pacific Cohort Studies Collaboration (APCSC) was established in the late 1990s when there was a distinct shortfall in evidence of the importance of risk factors for cardiovascular disease in Asia. With few exceptions, most notably from Japan, most of the published reports on cardiovascular disease in the last century were from Western countries, and there was uncertainty how far etiological associations found in the West could be assumed to prevail in the East. Against this background, APCSC was set up as a pooling project, combining individual participant data (about 600,000 subjects) from all available leading cohort studies (36 from Asia and 8 from Australasia) in the region, to fill the knowledge gaps. In the past 10 years, APCSC has published 50 peer-reviewed publications of original epidemiological research, primarily concerned with coronary heart disease, stroke, and cancer. This work has established that Western risk factors generally act similarly in Asia and in Australasia, just as they do in other parts of the world. Consequently, strategies to reduce the prevalence of elevated blood pressure, obesity, and smoking are at least as important in Asia as elsewhere - and possibly more important when the vast size of Asia is considered. This article reviews the achievements of APCSC in the past decade, with an emphasis on coronary heart disease. © 2012 World Heart Federation (Geneva). Publishedby Elsevier Ltd. All rights reserved.